Impact of Long-Term Nutrient Management on Soil N dynamics under Soybean – Wheat Cropping Sequence on a Vertisol - Risikesh Thakur, N.K. Khamparia; Muneshwar Singh, Satyabhan Kushwaha, S.D. Sawarkar (Journal of the Indian Society of Soil Science, 2017)
The present investigation was carried out at the Research Farm of Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh, India to study the nitrogen (N) dynamics in terms of total N, organic N fractions and N2 fixation in soil sample (0-0.30 m) collected from 39 year old long-term fertilizer experiment under soybeanâ€“wheat cropping sequence on a Vertisol. The experiment was commenced in June 1972. The present studies comprised of eight treatments i.e. 50% NPK, 100% NPK, 150% NPK, 100% NP, 100% N, 100% NPK+FYM, 100% NPKâ€“S and control with four replications, arranged in a randomized block design. The recommended dose of fertilizer for soybean and wheat being 20-80-20 and 120-80-40 of N:P2O5:K2O kg ha-1, respectively. The findings showed that applications of fertilizer alone and in combination with farmyard manure (FYM) significantly increased the organic carbon (OC), total N and N fractions (i.e. non-hydrolyzable N, amino acid N, hydrolyzable NH4+-N, hexose amine N) in both surface and sub-surface soils as compared to control plot. Among the various N fractions non-hydrolyzable N was dominant N fraction. The highest values of these fractions were found in 100% NPK + 15 t FYM ha-1 treatment. The relative contents of these fractions were in order : non-hydrolyzable N > amino acid N > hydrolzable NH4+-N > inorganic N (NH4+-N+NO3–N) > hexose amine N and it was higher in surface than the sub-surface soils. Further, the correlation studies revealed that the amino acid and hexose amine N fractions in surface soils and hydrolyzable NH4+-N and amino acid N fractions in sub-surface soils were better indices of soil N mineralization. Thus, the result clearly demonstrated that the sub-surface soils also substantially contributed to the N requirement of the crops. This was further supported by a better correlation between amino acid N in surface and hydrolyzable NH4+-N in the sub-surface soils with yield and N uptake by soybean and wheat crops.